2007
DOI: 10.1111/j.1740-0929.2007.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the characteristics of the carcass and the meat of the Chato Murciano pig and its cross with Iberian pig, reared indoors

Abstract: The Chato Murciano pig is a breed catalogued as a Special Protection breed in danger of extinction. At present it is commonly reared in an intensive system. We have studied the mineral composition and other characteristics of its carcass and meat. Samples from the Musculus longissimus lumborum were taken from a total number of 43 animals, divided into two groups, Chato Murciano and Chato Murciano crossed with Iberian, reared in a conventional indoor system. The resulting meat of the Chato Murciano pig and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 17 publications
3
19
2
Order By: Relevance
“…The groups reared indoors presented a higher pH, statistically significant (P N 0.05). The lower pH obtained, and the effect of the rearing system is in line with previous studies on this breed (Peinado et al, 2004;Poto et al, 2007;Galián et al, 2007), which suggests that these outdoor reared pigs experienced greater pre-slaughter stress (Barton-Gade and Blaabjerg, 1989;Gandemer et al, 1990;Edwards, 2005).…”
Section: Study Of Ph and Coloursupporting
confidence: 89%
“…The groups reared indoors presented a higher pH, statistically significant (P N 0.05). The lower pH obtained, and the effect of the rearing system is in line with previous studies on this breed (Peinado et al, 2004;Poto et al, 2007;Galián et al, 2007), which suggests that these outdoor reared pigs experienced greater pre-slaughter stress (Barton-Gade and Blaabjerg, 1989;Gandemer et al, 1990;Edwards, 2005).…”
Section: Study Of Ph and Coloursupporting
confidence: 89%
“…The mean values obtained in elements like K, Cu, Fe and Zn were similar to those obtained by other authors, who found values of 330-349 mg/100 g for K , 0.2 mg/100 g for Cu or 2.3 mg/100 g for Fe and 1.4 to 2.5-2.7 mg/100 g for Zn (Guang-Zhi et al, 2008). The values for P, Ca and Mg appeared at a higher quantity than in results obtained by Muñoz & Ledesma (2002), Galián et al (2007) and Poto et al (2007). The average values of Mn were 0.033 mg/100 g, level similar than those found by McCance & Widdowson's (1991), although lower than those recorded by Ramos (2008) in Peruvian Creole pigs (0.008 mg/100 g).…”
contrasting
confidence: 41%
“…The analysis of mineral composition was evaluated according to Galián et al (2007). Briefly, approximately 1 g of meat (LT) was used for the process of obtaining ashes in a furnace oven (Model HK-11; Herotec, Ahlen, Germany).…”
Section: Laboratorial Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm also the evidences from several studies (Serra et al 1998;Edwards 2005;Franci et al 2005;Estévez et al 2006) which suggested that traditional breeds having darker and redder color than commercial breeds. On the other hand some other authors as Poto et al (2003Poto et al ( , 2007 and Galián et al (2005Galián et al ( , 2007 comparing Chato Murciano with a Comercial breed, found that. Pigs raised outdoors presented darker meat than those raised indoors.…”
Section: Fat and Meat Colormentioning
confidence: 99%